Kuruluşundan bugüne D-8 örgütü - Güldal, Murat (My University, 2009)
D–8 Kalkınmakta olan sekiz ülkenin meydana getirdiği bir entegrasyondur. 1997 yılında İstanbul’da ilk toplantısını yaparak kuruluşunu gerçekleştirmiştir. Devlet başkanlarının oluşturduğu Zirve, Üye ülkelerin Dışişleri bakanlarının oluşturduğu Konsey, Hükümetlerce tayin edilen memurların oluşturduğu Komisyon ve sekterlik vazifesini yürüten Sekretarya, D–8 Örgütü’nü meydana getiren organlardır. Örgüt kuruluşundan günümüze kadar geçen zamanda beş zirve toplantısı, dokuz Bakanlar Kurulu toplantısı, yirmi kez de Komisyon toplantısı yapmıştır. Örgüt üyeleri arasında ticareti geliştirmek için Tercihli Ticaret Anlaşması ve Vize kolaylığı anlaşmaları imzalayıp üye ülkelerin Uluslararası ticaretlerini organize etmek için Uluslararası Pazarlama ve Ticaret şirketini kurmuştur. Örgüt genel anlamda bakıldığında kuruluşundan itibaren beklenilen düzeyde çalışmalar sergileyememiştir. Üye ülkelerin örgüt kuruluşunda görev alan yönetimlerinin değişmesi ile yerlerine gelen yeni yönetimlerin hedeflenen projeleri kendilerinden önceki siyasi iktidarların politik çalışmaları olarak düşünüp projelere alaka göstermemeleri örgütün başarı göstermesine engel olmuştur.

D–8 is an arrangement which is founded by eight developing countries. It actualized its foundation as holding the first meeting in Istanbul, in 1997. The principal organs of D–8 are: The Summit which is composed of the Heads of State/ Government of member states, The Council which is composed of the Ministers in charge of Foreign Affairs of member states, The Commission which is composed of senior officials appointed by their respective governments and the Secretariat which performs secretarial Works. During the time past from the foundation up to now, the organization held five summit meetings, nine ministerial meetings, and twenty commission meetings. In order to improve trade between the foundation members, Comparative Study of Trade and Visa convenience agreements are signed, and also, in order to organize the international trades between the member countries, International Marketing and Trade Company is established. Generally, the Organization could not show an expected performance since its foundation. It’s been a barrier to show success of the organization that next administrative managements which follows those managements took part in founding of the organization did not show an interest in the targeted projects, considering the projects as political workings of ex-managements.
Keywords: Örgütler_Ortadoğu; Tarih